(3QSGdI aj GdCeQ HGdTF hGdfgi Yf GdVOs - (3ejQRG CHh GdbGSe cdGfJQs
(3ChdgG (B:s
(3Gdbhd ai Cf GdCeQ HGdTF gd jbJVi Gdfgi Yf aYdg s
(3BNQgG (B:s
(3MJi jUjQ hGLHkG ef HGH GdebOeI ajUjQ aYdg MQGekG haGSOkG s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdMGOjI YTQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(130) s
Keywords: (3GdadSaI hGdefWbs